2010
DOI: 10.1103/physrevb.82.174105
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure x-ray diffraction andab initiostudy ofNi2Mo3N,Pd2

Abstract: Abstract:We have studied by means of high-pressure x-ray diffraction the structural stability of Ni 2 Mo 3 N, Co 3 Mo 3 N, and Fe 3 Mo 3 N. We also report ab initio computing modeling of the high-pressure properties of these compounds, Pd 2 Mo 3 N, and Pt 2 Mo 3 N.We have found that the nitrides remain stable in the ambient-pressure cubic structure at least up to 50 GPa and determined their equation of state. All of them have a bulk modulus larger than 300 GPa. Single-crystal elastic constants have been calcul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 39 publications
7
44
0
Order By: Relevance
“…From the EOS fit, we obtained the ambient pressure bulk modulus (B 0 ) and its pressure derivative B 0 as well as the unit-cell volume at ambient pressure (V 0 ). The EOS parameters are given in Table II together with the implied values for the second pressure derivative of the bulk modulus, B 0 [48]. These results suggest that wolframite-type InTaO 4 is less compressible than wolframitetype orthotungstates [22].…”
Section: Resultsmentioning
confidence: 92%
“…From the EOS fit, we obtained the ambient pressure bulk modulus (B 0 ) and its pressure derivative B 0 as well as the unit-cell volume at ambient pressure (V 0 ). The EOS parameters are given in Table II together with the implied values for the second pressure derivative of the bulk modulus, B 0 [48]. These results suggest that wolframite-type InTaO 4 is less compressible than wolframitetype orthotungstates [22].…”
Section: Resultsmentioning
confidence: 92%
“…49,50 On the other hand the most compressible axis of the HP phase is the c-axis which has a linear compressibility one order of magnitude larger than the b-axis (see Table 2). Additionally, we found that the monoclinic β angle of the HP phase is apparently not affected by compression.…”
Section: Resultsmentioning
confidence: 99%
“…This is common assumption in HP studies and will not affect the determination of the unit-cell parameter. 26 In Fig. 5, we show the residual of the refinement of the XRD experiment carried out at ambient pressure within the DAC.…”
Section: A Sample Characterizationmentioning
confidence: 99%